Tantangan Guru Sekolah Dasar Dalam Memahami Capaian Komponen Manajemen Sekolah - Muhammad Sufyan As-Tsauri; Chaerul Rochman; Maslani Maslani (IAIN Batusangkar, 2021)
One of the components that must be considered in improving the quality of education is the school management component. Some of the issues include school management components such as the competence of school principals, management of facilities and infrastructure, management of teachers and education personnel, financial management, curriculum management and management of student interests and talents. This study aims to determine the level of teacher understanding of the components of school management which consists of 14 statements as well as a real portrait of the condition of school management at the elementary level. The method used is descriptive quantitative. The data were obtained using questionnaire and interview techniques. Data analysis was performed using descriptive statistics, then triangulation was carried out on respondents and schools with the lowest scores. The sample used was 6 Islamic education teachers and 6 non-Islamic education teachers at the elementary level. The results showed that the understanding of the PAI teacher group was 3.3 greater than the non-Islamic Education teacher group of 2.8. The existing condition of school management for both Islamic Education and Non-Islamic Education teachers got the same scores of 3.3. Some of the lowest school management indicators were found, such as clean living habits in the school environment and sources of funding other than BOS funds (School Operational Fund). From these findings, the researcher has a recommendation to incorporate programs that have minimal achievements into the school’s vision and mission.